Estrogen stimulates adenosine receptor expression subtypes in human breast cancer MCF-7 cell line - Azam Mohamadi; Mahmoud Aghaei; Mojtaba Panjehpour (Wolters Kluwer Medknow Publications, 2018)
Estrogen is a steroid hormone that plays a key role in the development and regulation of reproductive system. It has been shown that estrogen is related to breast cancer development through binding to its receptors. In order to uncover the estrogen effects on adenosine receptor expression, estrogen-positive MCF-7 cells were used to treat with agonist and antagonist of estrogen and then the mRNA expression of adenosine receptor subtypes were evaluated. Estrogen-positive MCF-7 cells were treated with various concentrations of 17β estradiol (E2) as an estrogen agonist, and ICI 182,780 as an estrogen antagonist. The gene expression of adenosine receptor subtypes were detected by real time RT-PCR. The results of MTT assay showed that E2 increased cell viability in a dose dependent manner. The expression pattern of all adenosine receptor subtypes are as follow; A2b > A1 > A2a > A3 in untreated MCF-7 cells. Obtained results showed that E2 incubation at 0.001-0.01 μM led to up-regulation of A1ARs, A2aARs and A3ARs dose dependently. E2 at 0.001 μM also had no significant effect on A2bARs expression but, at higher doses induced a considerable decrease in mRNA A2bARs expression. Treatment with antagonist confirmed that up-regulation of these receptors is mediated by estrogen receptor. Taken together, our results indicate that treatment of MCF-7 cells with E2 led to up-regulation of adenosine receptors. However, these effects were partially restored by treatment with antagonist suggesting that such effects are mediated by estrogen receptors.